2017
DOI: 10.12659/msm.901926
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Penile Suspensory Ligamentous System Based on Visible Human Data Sets

Abstract: BackgroundThe aim of this study was to use a three-dimensional (3D) visualization technology to illustrate and describe the anatomical features of the penile suspensory ligamentous system based on the Visible Human data sets and to explore the suspensory mechanism of the penis for the further improvement of the penis-lengthening surgery.Material/MethodsCross-sectional images retrieved from the first Chinese Visible Human (CVH-1), third Chinese Visible Human (CVH-3), and Visible Human Male (VHM) data sets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…As Hoznek et al, 19 we found anteriorly the fundiform ligament with no function during erection. The absence of connection between the suspensory ligament and the tunica albuginea of the corpora cavernosa was confirmed by Chen et al 20 Posteroinferiorly to the suspensory ligament, we describe for the first time in medical literature a dense vertical ligament connecting the pubis symphysis to the tunica albuginea of the corpora cavernosa. The arcuate pubic ligament reinforces the attachments of the corpora cavernosa to the pubis symphysis, therefore having a similar function to the dense vertical ligament.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As Hoznek et al, 19 we found anteriorly the fundiform ligament with no function during erection. The absence of connection between the suspensory ligament and the tunica albuginea of the corpora cavernosa was confirmed by Chen et al 20 Posteroinferiorly to the suspensory ligament, we describe for the first time in medical literature a dense vertical ligament connecting the pubis symphysis to the tunica albuginea of the corpora cavernosa. The arcuate pubic ligament reinforces the attachments of the corpora cavernosa to the pubis symphysis, therefore having a similar function to the dense vertical ligament.…”
Section: Discussionsupporting
confidence: 79%
“…[12][13][14][15][16] Initial descriptions treat the penile ligament system as one entity without separating it its components. [17][18][19][20] Its function during penile erection was emphasized as stabilizing due to the firm adhesion to the pubic bone. 18 We dissected four entities in the suspensory system.…”
Section: Discussionmentioning
confidence: 99%
“…Due to heterogeneous anatomical descriptions in the literature, a complete yet concise review is necessary. The suspensory apparatus of the penis comprises three main components, which are, from anterior to posterior: the fundiform ligament of the penis, the suspensory ligament of the penis and the inferior pubic ligament [ 24 26 ]. They are represented in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The penile erective process requires the support of a group of complex structures which are closely related to the distribution of the fibrous connective tissue, consisting of mainly elastic fibers and bundles of collagen, which make the penis extensible (Hsieh et al, 2020). The function of the penis is also dependent on the fibers of the elastic system (Liu et al, 1993;Costa et al, 2006;Chen et al, 2017). Understanding the anatomical information of the elastic fibers in the penis would undoubtedly allow us to have a better treatment procedure of the erectile dysfunction (Qiao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%